Solid Biopolymer Electrolyte Based on k-Carrageenan for Electrochemical Devices Application - Shamsudin1, I.J.; Ahmad1, A.; Hassan1, N.H.; Kaddami3, H. (Asian Journal of Chemistry, 2014)
Solid biopolymer electrolyte based on kappa, k-carrageenan as the polymer host and ionic liquid 1-butyl-3-methylimidazolium chloride, [Bmim]Cl as the charge carrier has been successfully prepared. The ionic conductivity, (s) of the electrolytes significantly increase with the increase of weight percentage, (wt. %) of [Bmim]Cl. The highest s attained is 2.44 × 10-3 S cm-1 at ambient temperature. FTIR spectra confirmed the complexation and interactions of k-carrageenan and [Bmim]Cl. XRD diffractograms revealed that inclusion of [Bmim]Cl has increased the amorphous nature of k-carrageenan. SEM observations showed the smoother surface morphologies of the polymer electrolytes as the wt. % of [Bmim]Cl increases.